Formação de professor de inglês em contexto de projeto de extensão sobre prática de Tandem - Vieira, William Guimarães de Resende (2013)
In the context of education mediated by new technologies, information is available to anyone who may be interested in it, and the roles of student and teacher, especially in the last decade, have taken other contours. My work has an extension project developed in the context of language teaching and learning mediated by new technologies as its background, and it is aimed at analyzing my teacher education process as an active member of this project. I aim to understand, looking back to my own story, what was the impact that this extension project had either over my academic, personal and professional journeys. For that, I base myself on the conceptual framework of Dewey (1953) on Teacher Education and Reflective Practice, on Communities of Practice by Wenger (2000), as well as on the Theory of Engagement by Shneiderman (1994, 1998) and Kearsley (1997).